Successo formativo e accesso al lavoro: il lato oscuro della meritocrazia basata sulle competenze nel caso dei giovani affetti da una malattia cronica severa. - Bobbo, Natascia (Studi sulla Formazione/Open Journal of Education, 2022)
Academic successes and work accesses are defined in our society by a meritocratic system which should guarantee the advancement in some strategic positions only to those who possess a high level of key and specific competences, regardless of their identity or origin. At the same time, the acceleration of industrial, cultural, and productive transformations continues to raise the required performance levels. This contribution aims to deepen what could be the commitment that critical pedagogy can express towards those chronic ill adolescents and young who, despite some measures useful to compensate the meritocratic rules, rarely manage to reach a high level of marketable skills, exposing themselves to the risk of becoming poor adults.